The interaction effects between TLR4 and MMP9 gene polymorphisms contribute to aortic aneurysm risk in a Chinese Han population - Tan Li; Xu Zhang; Liang Sang; Xin-tong Li; Hai-yang Sun; Jun Yang; Yuan Yuan (BMC Cardiovascular Disorders, 2019)
Abstract Background A cross-talk between Toll-like receptor 4 (TLR4) and matrix metalloproteinase 9 (MMP9) plays a vital role in aortic pathophysiology. The objective of this study was to evaluate the interactions between TLR4 and MMP9 polymorphisms in the risk of aortic aneurysm (AA) and its subtypes. Methods KASP method was used to detect polymorphisms of TLR4 (rs11536889 and rs1927914) and MMP9 (rs17576) in 472 AA patients and 498 controls. According to location and size, AA patients were further classified into abdominal AA (AAA), thoracic AA (TAA), and large AA (>5.0 cm), small AA(≤5.0 cm), respectively. Results The significant interaction effect of TLR4rs1927914 with MMP9rs17576 polymorphisms was observed for the risk of TAA (P interaction  = 0.038, OR = 6.186) and large AA (P interaction  = 0.044, OR = 5.892). There were epistatic effects between TLR4rs1927914 and MMP9rs17576 polymorphisms on the risk of overall AA, AAA, TAA and large AA when they were present together. Moreover, the cumulative effects of the pairwise interaction TLR4rs1927914-MMP9rs17576 were associated with an increased risk of overall AA (P trend  = 0.032) and AAA (P trend  = 0.031). Conclusions The novel interaction between TLR4rs1927914 and MMP9rs17576 polymorphisms could increase the risk of AA disease or its subtypes by exerting epistatic and cumulative effects.